PENGARUH POLA ASUH ORANG TUA MILENIAL DENGAN RESILIENSI SISWA KELAS XI SMA NEGERI 1 BANDAR BATANG: PENGARUH POLA ASUH ORANG TUA MILENIAL DENGAN RESILIENSI SISWA KELAS XI SMA NEGERI 1 BANDAR BATANG - WIYANTO; Suyati, Tri; Lestari, Farikha Wahyu (Jurnal Psikoedukasia, 2023)
Wiyanto, "The Influence of Millennial Parenting Style on the Resilience of Class XI Students of SMA Negeri 1 Bandar Batang". Thesis for the Guidance and Counseling Study Program, Faculty of Education, PGRI University Semarang, 2023. This research is motivated by the level of resilience or resilience of students in addressing various life problems which are still low which are influenced by the upbringing of parents of SMA Negeri 1 Bandar Batang students, especially in class XI IPA. The purpose of this study was to find out whether there is an influence of parenting style on student resilience. This study uses a correlational quantitative approach. The population in this study were students of class XI IPA with a total of 180 students. Class XI IPA 1 is the class used for tryouts. the sample in this study were 124 students taken by simple random sampling technique. The data collection tools used were the student resilience scale and the parenting style scale. Based on the results of the study, it was found that there was a significant positive influence between millennial parenting and the resilience of class XI students at SMA Negeri 1 Bandar Batang. this is evidenced by the t count > t table, which is 0.587 with a significance value of 5% (0.00 <0.05). The coefficient of determination is 0.026, which means that 26% of student resilience is influenced by millennial parenting styles, while the rest can be influenced by other variables not examined in this study. Keywords: Parenting Style, Resilience.